A Follow-Up Study on the Continuity and Spillover Effects of Intimate Partner Violence During Pregnancy on Postnatal Child Abuse - Kita, Sachiko (Journal of interpersonal violence, 2021)
Previous studies have not focused on how intimate partner violence (IPV) during pregnancy predicts early postnatal child abuse. This study identifies the continuity and spillover effects of IPV during pregnancy on IPV and child abuse and neglect (CAN) at 1-month and 3-month postnatal periods. A total of 822 pregnant women were recruited at the third trimester of pregnancy at two obstetric hospitals in Tokyo, Japan, from June 2016 to September 2017. IPV during pregnancy and IPV and CAN at 1 month and 3 months postnatal were obtained through self-reported questionnaires. Results show that the rate of IPV was highest during pregnancy (16.4%), and there was significant continuance (69.4%) of this occurrence of IPV after childbirth (1 month: 13.9%; 3 months: 13.7%). In addition, the rate of CAN was 20.0% at 1 month postnatal and slightly increased at 3 months postnatal (21.8%). Furthermore, this study indicates that IPV during pregnancy was significantly associated with CAN at 1 month and 3 months postnatal (β = .16 and β = .14) and with IPV at 1 month (β = .68), and subsequently, IPV at 1 month was significantly associated with IPV at 3 months postnatal (β = .56). This study suggests the importance of conducting screenings for IPV during the perinatal period and providing intensive health interventions for abused women to support their parenting from pregnancy to 3 months postnatal to prevent or reduce CAN at 1 month and 3 months postnatal.